Evidences of the Defect Pool Model in the dark J-V characteristics of hydrogenated amorphous silicon based p-i-n devices - Sturiale, Alejandro Ernesto (2008)
In the scientific literature the density of states of hydrogenated amorphous silicon has been assumed to be either uniform or spatially variable inside the intrinsic layer of p-i-n solar cells. The dependence of the dark current voltage characteristics of amorphous silicon based solar cells with respect to the intrinsic layer thickness and to the mobility gap of a thin interfacial layer grown at the p/i interface is explored with numerical techniques. Our results indicate that the reported experimental trends can be adequately explained with the defect pool model and not by assuming an uniform density of states in the intrinsic layer.